Disrupting Surfaces of Nef Required for Downregulation of CD4 and for Enhancement of Virion Infectivity Attenuates Simian Immunodeficiency Virus Replication In Vivo - Iafrate, A. John (American Society for Microbiology (ASM), 2000)
The multifunctional simian and human immunodeficiency virus (SIV and HIV) Nef proteins are important for virulence. We studied the importance of selected Nef functions using an SIV Nef with mutations in two regions that are required for CD4 downregulation. This Nef mutant is defective for downregulating CD4 and, in addition, for enhancing SIV infectivity and induction of SIV replication from infected quiescent peripheral blood mononuclear cells, but not for other known functions, including downregulation of class I major histocompatibility complex (MHC) cell surface expression. Replication of SIV containing this Nef variant in rhesus monkeys was attenuated early during infection. Subsequent increases in viral load coincided with selection of reversions and second-site compensatory changes in Nef. Our results indicate that the surfaces of Nef that mediate CD4 downregulation and the enhancement of virion infectivity are critical for SIV replication in vivo. Furthermore, these findings indicate that class I MHC downregulation by Nef is not sufficient for SIV virulence early in infection.